Formation qualitative human resources as condition of effective management - Балановська, Т. І.; Гогуля, О. П.; Новак, О. В. (Scientific Progress & Innovations, 2012)
The composition of directors and specialists of agrarian enterprises was analyzed. Sociological research data of Ukrainian and foreign scientists on the managerial staff characteristics (their professional knowledge, skills, experience, qualifications) and their impact on the work efficiency was represented. The main requirements for the materials staff according to the survey results were presented. The data on preparation of specialists in agrarian and environmental branches was given. The need for forming of the high quality personnel was grounded.